PERPUTARAN MODAL KERJA, LIKUIDITAS DAN PROFITABILITAS PERUSAHAAN - Ahmad Juanda; Ginanjar Arief Setyabudi (Universitas Muhammadiyah Malang, 2020)
The purpose of this research is to examine the influence of working capital turn over and liquidity to profitability. The population in this research is all of the fast-moving consumer goods listed company in the Indonesian Capital Market Directory and publishes financial reports in 2016-2018. A sample is determined by a purposive sampling technique based on specified criteria and obtained as many as 24 companies. The research data is secondary data with the collection method uses documentation technique. Data analysis uses Multiple Linear Regression. The results show that working capital turn over (WCTO) and liquidity (CR) simultaneously have a significant effect on profitability (ROA) amount 34,6% while there remaining 65,4% is influenced by other factors. Partially, the working capital turn over (WCTO) variable has a significant effect on profitability (ROA) and liquidity (CR) variable has a significant effect on profitability (ROA).